Xenogeneic Bio‐Root Prompts the Constructive Process Characterized by Macrophage Phenotype Polarization in Rodents and Nonhuman Primates. Issue 5 (12th January 2017) - Li, Hui; Sun, Jingjing; Li, Jie; Yang, Hefeng; Luo, Xiangyou; Chen, Jinlong; Xie, Li; Huo, Fangjun; Zhu, Tian; Guo, Weihua; Tian, Weidong
Abstract : Tissue or organ regeneration using xenogeneic matrices is a promising approach to address the shortage of donor matrices for allotransplantation. Success of such approach has been demonstrated to correlate with macrophage‐mediated fibrotic homeostasis and tissue remodeling. The previous studies have demonstrated that treated dentin matrix (TDM) could be a suitable bioactive substrate for allogeneic tooth root regeneration. This study constructed xenogeneic bioengineered tooth root (bio‐root) via a combination of porcine TDM (pTDM) with allogeneic dental follicle cells (DFCs). Macrophage phenotypes are used to evaluate the remodeling process of xenogeneic bio‐roots in vitro and in vivo. pTDM can facilitate odontoblast differentiation of human derived DFCs. Xenogeneic bio‐roots in rat subcutaneous tissue prompt constructive response via M1 macrophage infiltration during early postimplantation stages and increase restorative M2 phenotype at later stages. After implantation of bio‐roots into jaws of rhesus monkeys for six months, periodontal ligament‐like fibers accompanied by macrophage polarization are observed, which are positive for COL‐1, Periostin, βIII‐tubulin and display such structures as fibroblasts and blood vessels. The reconstructed bio‐root possesses biomechanical properties for the dissipation of masticatory forces. These results support that xenogeneic bio‐root could maintain fibrotic homeostasis during remodeling process and highlight the potential application of xenogeneic matrices in regenerative medicine. Abstract : Xenogeneic bio‐root constructed of porcine treated dentin matrix seeded with allogeneic dental follicle cells prompts a constructive process characterized by macrophage‐mediated fibrotic homeostasis in vitro and in vivo. The reconstructed xenogeneic bio‐root in jaw of rhesus monkeys not only facilitates the periodontal ligament‐like fibers reconstruction but also exhibits positive biomechanical properties for the dissipation of masticatory forces.